Atherosclerotic Components in Thrombi Retrieved by Thrombectomy for Internal Carotid Artery Occlusion Due to Large Artery Atherosclerosis: A Case Report - Eto, Futoshi; Koge, Junpei; Tanaka, Kanta; Yoshimoto, Takeshi; Shiozawa, Masayuki; Hatakeyama, Kinta; Toyoda, Kazunori; Koga, Masatoshi (Frontiers in Neurology, 2021)
Introduction: The correlation between the composition of thrombi retrieved by mechanical thrombectomy (MT) and stroke etiology is inconclusive. We describe a case with atherosclerotic components in thrombi retrieved by MT for acute internal carotid artery (ICA) occlusion. Case Presentation: A 69-year-old man underwent MT for acute left ICA occlusion. Successful reperfusion was achieved by five passes using stent retrievers and the aspiration catheter. A large volume of red thrombus was retrieved by each pass. The final angiogram showed successful reperfusion with modified Thrombolysis in Cerebral Ischemia grade 2b and severe stenosis in the proximal ICA. Neck magnetic resonance imaging showed severe left ICA stenosis with a vulnerable plaque. Hence, his stroke etiology was determined as large artery atherosclerosis. Histopathological examination of the retrieved thrombi revealed atheromatous components, including cholesterol clefts, foam cells and a necrotic core. Conclusions: Atherosclerotic components in retrieved thrombi might provide useful clues for diagnosing stroke pathogenesis. Further studies are warranted to clarify the utility of assessing atheromatous components in retrieved thrombi in diagnosing stroke etiology.